ANALISIS TEKNIK RENDERING MENGGUNAKAN MENTAL RAY DAN ARNOLD PADA FILM ANIMASI 3D "GARA-GARA HOAX" - Rahmi Santy Nazir; Afdhol Dzikri; Oktavianto Gustin (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2018)
The final result in the creation of 3D animation is the rendering process in which the result of the rendering determines the final result of the created movie. 3D animation will surely pass through the process of rendering which is a very important process commonly used by the world of animated cinema. Each animation uses a different rendering engine depending on rendering using what rendering engine. In this study will generate rendering of rendering time from rendering using mental ray and arnold on 3D animation film "Because of HOAX". In addition, this study will also compare the results of the size per scene of both rendering techniques are mental ray and arnold. The way it works is to run one by one rendering using Autodesk Maya, then compare the render results in the size of each scene, the length of time renders from each render. The results of this test that rendering techniques using arnold is superior in terms of size size per scene, because arnold save the file memory is not too much. While the rendering speed of mental ray faster than the arnold although the time difference is not much different.